The Effect of Using Mental Maps On Cognitive Achievement In Rhythmic Gymnastics - Mohsen, Noha (Journal of Physical Education, 2017)
The aim of the research was to design mental maps for some theoretical ofcognitive achievement in the gymnastic game and to identify the effect of the use of mentalmaps on cognitive achievement. The researcher hypothesized that there were statisticallysignificant differences between the results of the two tests and the existence of significantdifferences in the remote tests between the control and experimental research in the results ofthe tests of collection and retention. The study sample consisted of two experimental andexperimental groups who are students of the second stage in the Faculty of PhysicalEducation and Sports Sciences. The researcher adopted the achievement results in the firstexam and the retention test for the most committed female students in attendance andattending the theoretical exams, with a total of (12) students from each group. Theapplication of the teaching method continued through the method of mental maps throughoutthe period of theoretical theorems, which included the first half hour of the first chapter ofthe experimental group, while the control group adopted the method of explanation used bythe teachers of the article. And the same date as the theoretical exam.Through the results obtained by the researcher and their analysis and discussionof the results, we concluded that the mental map is effective in improving students'achievement in the cognitive part. Teaching using the mental map is also suitable forteaching theoretical subjects in the field of Gymnastics better than the usual methods. Themethod used in the teaching of theoretical subjects in the subject of Gymnastics is useful interms of information acquisition, but weak in terms of retention of information. Finally, themethod of teaching using mental map strategies is of great benefit in terms of retention ofacquired material. The researcher recommended the necessity of adopting the strategy of themental map in teaching the theoretical material of the Gymnastics and spreading this strategyto the rest of the materials. In addition to that, training teachers of materials, especiallyprofessors of theoretical subjects in courses on the use of mental map as well as theintroduction of teaching methods mental maps within the vocabulary of teaching methods inthe Faculty of Physical Education and Sports Science.